Bioactive chemical compounds in Eremurus persicus (Joub. & Spach) Boiss. essential oil and their health implications - Salehi, B.; Ayatollahi, S. A.; Segura-Carretero, A.; Kobarfard, F.; Contreras, M. d. M.; Faizi, M.; Sharifi-Rad, M.; Tabatabai, S. A.; Sharifi-Rad, J. (Cellular and Molecular Biology, 2017)
The genus Eremurus is native to Eastern Europe and temperate Asia. Particularly, Eremurus persicus (Joub. & Spach) Boiss. is highly valued in traditional foods and medicine. Scientific knowledge about E. persicus chemical composition and bioactivity is required. Therefore, the present study is aimed to determine the volatile composition of E. persicus essential oil (EO) by means of gas chromatography coupled to flame ionization/mass spectrometry detection. Moreover, the antioxidant, antimicrobial, anticancer, and acetylcholinesterase inhibitory activities of the EO were tested. Interestingly, the anti-dermatophyte potency was close to that of the drug griseofulvin, with minimum fungicidal concentration ranging between 0.7 and 4.5% depending on the fungi strain. The EO was also effective against hepatocellular carcinoma (Hep-G2) and breast adenocarcinoma (MCF-7) human cancer cell lines in a concentration (200-1500 ng/mL)-dependent manner, with a decrease of the cell viability up to 65% and 52%, respectively. The E. persicus EO was rich in terpenes and oxygenated terpene derivatives. Individually, limonene (16.25%), geranylgeraniol (15.23%), n-nonanal (9.48%), geranyl acetone (9.12%), benzene acetaldehyde (8.51%), linalool (7.93%), Î±-pinene (6.89%), and 1,8-cineol (5.22%) were the most abundant volatile compounds and could be chosen as analytical markers of this essential oil. In conclusion, our results suggested that this EO possesses a wide range of bioactive properties that could be useful in nutraceutical, functional foods and cosmeceutical formulations.